The Effect of Massage Therapy in Overcoming Constipation in Infants Aged 7-12 Months - Yulrina Ardhiyanti Ririn; Nur Israyati (Science Midwifery, 2021)
Constipation is a problem that often occurs in children and is a burden worldwide because of its increasing prevalence, the prevalence is estimated at 0.3% -8%. The prevalence of constipation in children up to 1 year of age reaches 2.9% and increases in the second year by about 10.1%. Massage as an alternative medicine is one of the constipation therapies. This study aims to determine the effect of massage therapy on constipation in infants aged 7-12 months at the Arrabih Pratama Clinic Pekanbaru. This type of research is quantitative with a Quasi Experiment design using a pretest and posttest. The population and sample of this study were babies aged 7-12 months who experienced constipation who visited the Arrabih Pratama Clinic Pekanbaru in July-December 2020, totaling 24 people. The type of data in this study is primary data, with univariate, bivariate data analysis, the hypothesis test used is the independent T test (paired sample test). The results obtained showed that there was an effect of massage therapy in overcoming constipation for infants aged 7-12 months before and after massage therapy, there was a significant difference in constipation for infants aged 7-12 months between the intervention group and the control group. It is hoped that health workers, especially midwives as providers of maternal and child health services, are expected to socialize the provision of massage therapy in dealing with children's complaints before administering pharmacological therapy.